A Hybrid Online Intervention for Reducing Sedentary Behavior in Obese Women - Adams, Melanie M.; Davis, Paul G.; Gill, Diane L. (Frontiers in Public Health, 2013)
Sedentary behavior (SB) has emerged as an independent risk factor for cardiovascular disease and type 2 diabetes. While exercise is known to reduce these risks, reducing SB through increases in non-structured PA and breaks from sitting may appeal to obese women who have lower self-efficacy for PA. This study examined effects of a combined face-to-face and online intervention to reduce SB in overweight and obese women. A two-group quasi-experimental study was used with measures taken pre and post. Female volunteers (M age = 58.5, SD = 12.5 years) were enrolled in the intervention (n = 40) or waitlisted (n = 24). The intervention, based on the Social Cognitive Theory, combined group sessions with email messages over 6 weeks. Individualized feedback to support mastery and peer models of active behaviors were included in the emails. Participants self-monitored PA with a pedometer. Baseline and post measures of PA and SB were assessed by accelerometer and self-report. Standard measures of height, weight, and waist circumference were conducted. Repeated measures ANOVA was used for analyses. Self-reported SB and light PA in the intervention group (I) changed significantly over time [SB, F(1, 2) = 3.81, p = 0.03, light PA, F(1, 2) = 3.39, p = 0.04]. Significant Group × Time interactions were found for light PA, F(1, 63) = 5.22, p = 0.03, moderate PA, F(1, 63) = 3.90, p = 0.05, and for waist circumference, F(1, 63) = 16.0, p = 0.001. The intervention group decreased significantly while the comparison group was unchanged. Hybrid computer interventions to reduce SB may provide a non-exercise alternative for increasing daily PA and potentially reduce waist circumference, a risk factor for type 2 diabetes. Consumer-grade accelerometers may aide improvements to PA and SB and should be tested as part of future interventions.